Mechanism of Action, Resistance, Synergism, and Clinical Implications of Delamanid Against Multidrug-Resistant Mycobacterium tuberculosis - Khoshnood, Saeed; Taki, Elahe; Sadeghifard, Nourkhoda; Kaviar, Vahab Hassan; Haddadi, Mohammad Hossein; Farshadzadeh, Zahra; Kouhsari, Ebrahim; Goudarzi, Mehdi; Heidary, Mohsen (Frontiers in Microbiology, 2021)
Multi drug-resistant (MDR) isolates of Mycobacterium tuberculosis (MTB) are one the main global threat in the end tuberculosis (TB) era. Delamanid (DLM) is a nitro-dihydro-imidazooxazole derivative used for treatment of MDR-TB. DLM has distinct mechanism of action, inhibiting methoxy- and keto-mycolic acid synthesis through F420 coenzyme Mycobacteria system and generating nitrous oxide. Although DLM resistance among MTB stains is uncommon, there are increasing reports in Asia and Europe and such resistance will prolonged the treatment courses of patients infected with MDR-TB. In this review, we will narrate the anti-mycobacterial properties of DLM, report the global prevalence of DLM resistance, discuss synergism of DLM with other anti-TB drugs, and evaluate the documented clinical trials to provide new insights into the clinical use of this antibiotic.